«Ja em vaig aplatanant»: l'exil colombien de Ramon Vinyes (1940-1950) - Gilard, Jacques (Caplletra. Revista Internacional de Filologia, 2004)
This article analyzes in detail the new period of exile of Ramon Vinyes inBarranquilla (1940-1950): Franco’s victory forces him to seek exile and return again to Colombia, where the longing for the lost fatherland and the distance from his family and Colombian society provoke in him a feeling of apathy. But also at that time he creates a narrative style that may be said to belong to the initial stirrings of what will later be called Magic Realism.